Is it Possible to Attribute International Liability to States Accused of Committing Terrorist Acts? - Alcaide Fernández, Joaquín (2009)
This paper analyzes the potential attribution of international liability to States for the commission of terrorist acts. To this end, the author develops the international obligations in the fight against terrorism, their content, limitations and conventional and non-conventional normative frameworks. The author also analyzes the connection between the commission of a violation of an international obligation relating to the prevention and suppression of terrorism and the attribution of State liability.